Cleaning And Sterilization Of Sheep Wool Fiber Using Supercritical Carbon Dioxide - Allafi, Faisal Aboelkasim Salem (2022)
Sheep wool is utilized as a textile material for clothing and high-quality fabric in the modern textile industry. Raw sheep wool contains dirt, suint and wax. Thus it requires an effective cleaning process to remove contaminants. Existing sheep wool processing requires a huge amount of fresh water and the addition of toxic chemicals which results in the generation of toxic effluent and wool fibre damage. Besides, contaminates with pathogenic bacteria. Therefore, it is urged for an effective technology to eliminate pathogenic microorganisms for safe handling. In this study, supercritical carbon dioxide scCO2 was used to treat sheep wool fibre as a waterless and effective alternative to existing sheep wool processing. The pathogenic bacteria in sheep wool fibre were determined using molecular identification with ribosomal ribonucleic acid 16sRNA. The influences of scCO2 sterilization and cleaning of sheep wool fibre were determined with varying pressure (10-40 MPa), temperature (32-80 oC), and treatment time (30-90 min). Subsequently, the physicochemical, thermo-mechanical properties and surface morphology of scCO2 treated and untreated fibre were determined using various analytical means.